2018
DOI: 10.1097/md.0000000000011816
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility and Efficacy of Transient Elastography using the XL probe to diagnose liver fibrosis and cirrhosis

Abstract: Background:Transient elastography (TE) has been validated as an effective noninvasive tool for the assessment of liver fibrosis. The XL probe is a new probe that was initially designed for use in patients with obesity. A meta-analysis was performed to assess the feasibility and efficacy of TE using the XL probe.Methods:In September 2016, we systematically searched the PubMed and Science Direct search engines. The feasibility of TE was evaluated based on the failure rate and the results of the unreliable liver … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 39 publications
0
14
0
Order By: Relevance
“…The development of the XL probe has improved the usefulness of TE in this population; however, limitations remain. In a meta‐analysis of studies comparing the use of the XL probe to the M probe, the former was found to have lower rates of failure in patients with a BMI ≥30 kg/m 2 (RR 0.16, 95% CI 0.08‐0.32, P < .00001) . However, the rates of unreliable measurements were not significantly different between the two probes (RR 0.63, 95% CI, 0.30‐1.32, P = .22).…”
Section: Methodsmentioning
confidence: 98%
“…The development of the XL probe has improved the usefulness of TE in this population; however, limitations remain. In a meta‐analysis of studies comparing the use of the XL probe to the M probe, the former was found to have lower rates of failure in patients with a BMI ≥30 kg/m 2 (RR 0.16, 95% CI 0.08‐0.32, P < .00001) . However, the rates of unreliable measurements were not significantly different between the two probes (RR 0.63, 95% CI, 0.30‐1.32, P = .22).…”
Section: Methodsmentioning
confidence: 98%
“…LS measurements were made with TE (Fibroscan, EchoSens, Paris, France) using a LOGIQ S8 US scanner in two sessions. The standard M probe was used for all participants unless the use of an XL probe was recommended by the scanner [ 21 ].…”
Section: Methodsmentioning
confidence: 99%
“…Earlier studies suggested that the failure rate of TE was lower in obese patients with the use of XL probe 45 . A study by Wong et al suggested that the median LSM obtained by M and XL probes were nearly identical at each fibrosis stage when M probe was used in patients with BMI < 30 kg/m 2 and XL probe was used in those with BMI ≥ 30 kg/m 2 46 .…”
Section: Discussionmentioning
confidence: 95%